PELATIHAN PENYUSUNAN CURRICULUM VITAE (CV) DAN PERSIAPAN WAWANCARA KERJA BAGI SISWA SMK - Ika Rachmawati; Adiguna Sasama Wahyu Utama; Nunuk Latifah; Anna Widayani (P3M Politeknik Negeri Malang, 2024)
SMK PGRI 4 Blitar City is one of the private vocational high schools in Blitar. As a provider of vocational education, SMK PGRI 4 Blitar City hopes that its graduates will be immediately accepted, both in the business sectors and industrial sectors. Based on the initial observations, the number of students who know the importance of preparing job application documents and the job selection process well is still few, so it is necessary to effectuate training in CV arrangement and job interviews preparation for students at SMK PGRI 4 Blitar City. This activity was organized to provide knowledge about preparing job application documents and techniques for facing the job selection process for students, awareness that by understanding the method for preparing job application documents and deal with job selection, students will find it easier to get a job after graduating from school, as well as improving students' abilities in compiling job application documents, especially CVs and preparing for job interview. This activity was attended by 44 students of SMK PGRI IV Blitar City. It was carried out in two stages, namely counseling and training. The results of observations and filling out questionnaires by participants showed that overall, the implementation of the training activities had been successful.